Piracy in the Gulf of Aden and the Arabian Sea - Sakhuja, Vijay (Emirates lecture series, 2013)
"The contemporary discourse on maritime security is highly focused on asymmetric threats and challenges confronting the international community. Among these, terrorism and sea piracy have attracted greater attention. These issues have figured prominently in statements and speeches by the political leaderships across the globe and international organizations such as the United Nations, which have attempted to address it through a number of resolutions and conventions, and the national security strategy documents of several countries have incorporated these in their strategic calculations and operational doctrines. The international community has responded firmly to these threats and challenges through a number of political, diplomatic, security, legal and financial initiatives with positive results. Likewise, the international shipping industry has expressed concern about the threat of piracy and joined hands with the governments and instituted best business practices to protect ships against pirate attacks"--Summary.